ДЕПРЕССИЯ МАНЫЧА КАК ОБЛАСТЬ МИГРАЦИЙ ФАУН ПОНТО-КАСПИЯ В ПЛЕЙСТОЦЕНЕ - Янина Т.А. (My University, 2006)
During the Pleistocene, the Manych depression served repeatedly as a strait connecting the Caspian and the Black seas basins. The geological structure and fossil mollusks give evidence of in interactions between these basins. Migration of Caspian mollusks to the Black Sea dominated over the backward one.
Keywords: Кайнозой::Четвертичная::Плейстоцен